Challenges of Food Security and Increasing Urbanization: Reliance on Peri-Urban Agriculture (PUA) - K. G, Kute; Begum, Mohammedi (Journal of Agricultural Extension Management, 2023)
As the world population is growing rapidly and urbanization is increasing, food security is becoming a major challenge. Accessibility, Affordability and Availability of food are the three core aspects of food security. Peri-Urban agriculture (PUA) can become an important source of nutritionally adequate and culturally acceptable food for urban populations. However, the problems like limited recognition, land conversion, water pollution and increasing competition from other sectors for limited natural resources pose a threat to the potential of PUA to contribute to urban resilience. Tackling food security needs analysis of all the different levels of a food system such as food production, processing, distribution and consumption. When assumed, high awareness of healthy food in PUA-derived markets, the loss of locally produced and highly perishable food is reduced due to shorter supply chains thereby contributing to the reduction in overall food waste. According to the projection, India’s urban population would increase by a total of 400 million by 2050. Using peri-urban regions has emerged as the need of the hour, and innovations like vertical farming and hydroponics both contribute to an increased availability of nutritious food. Urban and Peri-Urban Agriculture (PUA) are generally not a choice; they are means of survival, providing people not only with food, but also a living. The abstract concludes by suggesting that peri-urban agriculture has the potential to contribute to a sustainable and resilient food system in the face of global challenges